Teachers And Students’ Beliefs About English Homework In 9th Grade, In A Public Institution Of Calarca, Quindio. (2016)
Bearing in mind all the importance that English has had worldwide, it is necessary to analyze the didactics that happen inside English between students and teachers. Thus, this research has been developed in order to describe the teachers’ and students’ beliefs about English homework in a public institution from Calarcá, Quindío. This study has been applied to 17 students who were in 9th grade from the Calarcá public institution, and 7 teachers from different public institutions. This study holds a qualitative approach and has a micro ethnographic design. The instruments used in this study were two surveys, one conducted to students and the other to the teachers. By means of these surveys it was found that students’ and teachers’ beliefs about English homework were that homework is a tool of reinforcement event that needed to be modified in order to accomplish students’ academic demands.